Proof of Concept (PoC) 1.0—Implementing a bioshading system design method - Oliveira, M. J.; Rato, V.; Leitão, C. (Biomimetics, 2021)
Nature provides a remarkable database of possible adaptation strategies that can be implemented in biomimetic design of shading systems. However, at this moment, successful design methods are conditioned to a limited knowledge and ability to emulate nature’s strategies to meet corresponding functional needs. The implementation of biomimetic processes has some major challenges: (1) the search and selection among several databases of appropriate strategies adopted by nature; (2) difficulties in reading, interpreting and translating at different scales; (3) connection problems between concepts and material premises. The selection of nature models is a very common situation among architectural projects. Proof of Concept (PoC) 1.0 was the first experience of application of the Bioshading System Design Method (BSDM). BSDM is a problem-based method that guides its users since the initial architectural challenge definition, improving users’ capabilities to interpret and translate nature strategies into architecture design, until its final state of creation, it’s physical condition. This experience enabled us to validate and evolve initial decisions, based on users experience and evaluation. At the end, PoC 1.0 revealed to be a fundamental step into the final version of BSDM.